Resistance Development in Multi-Drug Resistant Bacteria to Antimicrobials from Methanolic Extract of The Stem Bark of Artocarpus altilis - Temidayo E, Adetayo; Chidinma O, Nnoli; Adeniyi A, Ogunjobi (The International Journal of Biotechnology, 2021)
Antibiotics for many years were known to be effective against different strains of bacteria and other microbes. The discovery of antibiotics has led to a severe reduction in death and disease. However, the indiscriminate use of antibiotics resulted in the development of resistance and multiple resistances by bacteria hence, the search for alternative therapy for the treatment of infectious diseases making researchers shift their attention to plant antimicrobials. Nevertheless, the possibility of bacteria developing resistance to plant antimicrobials is not well studied. This study aims to evaluate the development of resistance in multi-drug resistant bacteria to antimicrobials from the methanol extract of the stem bark of Artocarpus altilis. The susceptibility of multi-drug resistant Staphylococcus epidermis, Escherichia coli, Bacillus cereus, Staphylococcus saprophyticus, Proteus mirabilis and Pseudomonas aeruginosa to methanol extract of Artocarpus altilis at different concentrations (160mg/l, 80mg/l, 40mg/l and 20mg/ml) was tested after which the bacteria were exposed to a sub-lethal concentration over some time. The result displayed that Proteus mirabilis showed no sensitivity at all concentrations after eighteen days of exposure. In comparison, the other bacterial test isolates only showed activity at 160mg/ml and 80mg/ml after 24 days of exposure except for Bacillus cereus, which showed activity at the lowest concentration (20mg/ml). This study demonstrated that exposure of bacteria to antimicrobial plant extract at a sub-lethal concentration could induce the development of resistance.